Genomic Epidemiology of Campylobacter jejuni Transmission in Israel - Rokney, Assaf; Valinsky, Lea; Moran-Gilad, Jacob; Vranckx, Katleen; Agmon, Vered; Weinberger, Miriam (Frontiers in Microbiology, 2018)
Objectives: Campylobacter jejuni is responsible for 80% of Campylobacter infections in Israel, a country with a high incidence reaching 91/100,000 population. We studied the phylogeny, diversity and prevalence of virulence factors using whole genome sequencing (WGS) of a national sample of C. jejuni clinical, food and animal isolates collected over a 10-year period (2003-2012). Methods: C. jejuni isolates (n=263) were subject to WGS using Illumina sequencing (PE 250bpx2). Raw reads and de-novo assemblies were analyzed with the BioNumerics whole genome MLST (wgMLST) pipeline. Reads were screened for 71 virulence genes by the SRST2 script. Allelic profiles were analyzed to create minimum spanning trees and allelic core distances were investigated to determine a reliable cutoff for strain determination. Results: wgMLST analysis of 263 C. jejuni isolates indicated significant diversity among the prevalent clonal complex (CCs) with CC-21 and CC-353 being the most diverse, and CC-574 the most clonal. Within CC-21, sequence type (ST)-1359 created a separate clade. Human, poultry and bovine isolates clustered together across the different STs. Thirty nine percent of studied isolates were assigned to 29 genetic clusters. Temporal and geographical relatedness were found among the minority of clusters, while most phylogenetically associated cases appeared diffuse and unassociated epidemiologically. The majority of virulence factors were highly prevalent across the dataset and not associated with genotype, source of isolation or invasiveness. Conversely, all 13 genes associated with type VI secretion system (T6SS) were lineage-related and identified in only 18% of the isolates. T6SS was detected in 95.2% of ST-1359, a common type in Israel Conclusions: wgMLST supported the assessment that poultry and cattle are likely food sources of infection in Israel. Substantial genetic clustering among C. jejuni isolates suggested multiple point source and diffuse outbreaks that were previously unreported in Israel. The high prevalence of T6SS among ST-1359 isolates is unique to Israel, and requires further investigation. This study exemplifies the importance of studying foodborne pathogens using advanced genomic approaches across the entire spectrum of One Health.